Quel est l’impact de la faim et de la lutte pour la survie sur le rapport subjectif au travail ? - Valérie Ganem; Martha Veras Rodrigues (Perspectives Interdisciplinaires sur le Travail et la Santé)
Based on a work psychodynamics study conducted in 2013 with Brazilian construction workers, the following hypothesis is proposed: the defensive ideology known as “the struggle for survival” has a considerable impact on the subjective relation to work. This article thus continues a 30-year-old dialogue between work psychodynamics and work anthropology in search of new elements to help us better understand the subjective relation that today’s Brazilian workers have with work.